Peran Stimulasi Dini terhadap Perkembangan Motorik Kasar dan Halus Anak Usia Dini - Husaen, Rinelsa R. (Peneliti.net, 2024)
This study aims to explore the role of early stimulation in enhancing gross and fine motor development in early childhood. Motor development is a fundamental aspect of child growth, directly influencing physical coordination, cognitive performance, and future learning readiness. Through a qualitative descriptive approach, this research was conducted in a group of early childhood education institutions (PAUD) using observation, interviews, and documentation as data collection methods. The findings reveal that children who receive consistent, contextual, and playful stimulation show significantly more advanced motor skills compared to those who do not. Effective stimulation includes activities such as drawing, threading beads, running, and role-playing, all of which engage children in meaningful and enjoyable learning experiences. Moreover, the involvement of educators and parents in the stimulation process significantly enhances its impact, reinforcing the importance of a collaborative approach between home and school environments. This study reinforces previous theories by Papalia and Feldman (2011) and Hurlock (2003) and contributes new insights by highlighting the value of interactive and contextual stimulation. The results suggest that early stimulation should be an integral component of early childhood education programs and supported by structured planning and continuous evaluation. This research offers practical recommendations for educators and policymakers aiming to foster optimal motor development in young children..